Improved PCR-Based Subtractive Hybridization Strategy for Cloning Differentially Expressed Genes. (August 2000) - Zhu, F.; Yan, W.; Zhao, Z.L.; Chai, Y.B.; Lu, F.; Wang, Q.; Peng, W.D.; Yang, A.-G.; Wang, C.J.
An improved PCR-based subtractive hybridization strategy was used to clone apoptosis-related genes induced by all-trans retinoic acid (ATRA) from human promyelocytic leukemia cell line HL-60 cells. The protocol used the cap-finder method, longdistance PCR, streptavidin magnetic beadmediated subtraction and spin column chromatography. Twenty-seven clones related to apoptosis were identified by reverse dot blot assay. Seventeen were known genes, of which seven have been reported to be apoptosis related. The remaining 10 were unknown genes, five of which were sequenced and named apr-1 to apr-5. apr-1, apr-2, apr-3 and TNF were reidentified by reverse dot blot, and it is suggested that they might be related to apoptosis. The results suggest that this strategy might be efficient for large-scale cloning of differentially expressed genes in target cells.